Redox Mediator with the Function of Intramolecularly Disproportionating Superoxide Intermediate Enabled High‐Performance Li–O2 Batteries (Adv. Energy Mater. 12/2022). Issue 12 (24th March 2022) - Sun, Zongqiang; Lin, Xiaodong; Dou, Wenjie; Tan, Yanyan; Hu, Ajuan; Hou, Qing; Yuan, Ruming; Zheng, Mingsen; Dong, Quanfeng
Abstract : Li–O2 Batteries In article number 2102764, Quanfeng Dong and co‐workers propose the use of a high‐efficiency redox mediator with the function of mediating superoxide intermediates as a bifunctional solution‐phase catalyst for Li–O2 batteries, which provides a useful reference for the design and development of multifunctional O2 catalysts for metal–air batteries.